mx+my+nx+ny
2a-ax+2d-dx
xy-4y-py+4p
12a+3k-4ac-ck
12c-30cx+42c+2t-5tx+7t
Объяснение:
просто переумножаем
a) (m+n) (x+y) =mx+my+nx+ny
b) (a+d) (2-x) = 2a-ax+2d-dx
с) (x-p) (y-4) =xy-4x-py+4p
d) (4a+k) (3-c) = 12a-4ac+3k-ck
e) (6c+t) (2-5x+7) =6c(2-5x+7) +t(2-5x+7) = 12c-30cx+42c+2t-5tx+7t=54c-30cx+9t-5tx
mx+my+nx+ny
2a-ax+2d-dx
xy-4y-py+4p
12a+3k-4ac-ck
12c-30cx+42c+2t-5tx+7t
Объяснение:
просто переумножаем
a) (m+n) (x+y) =mx+my+nx+ny
b) (a+d) (2-x) = 2a-ax+2d-dx
с) (x-p) (y-4) =xy-4x-py+4p
d) (4a+k) (3-c) = 12a-4ac+3k-ck
e) (6c+t) (2-5x+7) =6c(2-5x+7) +t(2-5x+7) = 12c-30cx+42c+2t-5tx+7t=54c-30cx+9t-5tx